Metabolomic Profile of the Healthy Eating Index-2015 in the Multiethnic Study of Atherosclerosis - Gadgil, Meghana D; Wood, Alexis C; Karaman, Ibrahim; Graça, Goncalo; Tzoulaki, Ioanna; Zhong, Victor W; Greenland, Philip; Kanaya, Alka M; Herrington, David M (The Journal of nutrition, 2023)
Poor diet quality is a risk factor for type 2 diabetes and cardiovascular disease. However, knowledge of metabolites marking adherence to Dietary Guidelines for Americans (2015 version) are limited. The goal was to determine a pattern of metabolites associated with the Healthy Eating Index (HEI)-2015, which measures adherence to the Dietary Guidelines for Americans. The analysis examined 3557 adult men and women from the longitudinal cohort Multiethnic Study of Atherosclerosis (MESA), without known cardiovascular disease and with complete dietary data. Fasting serum specimens and diet and demographic questionnaires were assessed at baseline. Untargeted H 1-dimensional nuclei magnetic resonance spectroscopy (600 MHz) was used to generate metabolomics and lipidomics. A metabolome-wide association study specified each spectral feature as outcomes, HEI-2015 score as predictor, adjusting for age, sex, race, and study site in linear regression analyses. Subsequently, hierarchical clustering defined the discrete groups of correlated nuclei magnetic resonance features associated with named metabolites, and the linear regression analysis assessed for associations with HEI-2015 total and component scores. The sample included 50% women with an mean age of 63 years, with 40% identifying as White, 23% as Black, 24% as Hispanic, and 13% as Chinese American. The mean HEI-2015 score was 66. The metabolome-wide association study identified 179 spectral features significantly associated with HEI-2015 score. The cluster analysis identified 7 clusters representing 4 metabolites; HEI-2015 score was significantly associated with all. HEI-2015 score was associated with proline betaine [β = 0.12 (SE = 0.02); P = 4.70 × 10 ] and was inversely related to proline [β = -0.13 (SE = 0.02); P = 4.45 × 10 ], 1,5 anhydrosorbitol [β = -0.08 (SE = 0.02); P = 4.37 × 10 ] and unsaturated fatty acyl chains [β = 0.08 (SE = 0.02); P = 8.98 × 10 ]. Intake of total fruit, whole grains, and seafood and plant proteins was associated with proline betaine. Diet quality is significantly associated with unsaturated fatty acyl chains, proline betaine, and proline. Further analysis may clarify the link between diet quality, metabolites, and pathogenesis of cardiometabolic disease.